Pengembangan Pemasaran Sayuran Organik pada CV Reja Mayur Melalui Sosialisasi Green Marketing - Hilman Hasibur Rohman; Eliada Samuel Pasaribu; Muhammad Rifal Ramadhan; Autika Pramesti Ayu Hadi Pratiwi; Fatchur Rozci (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
The growing awareness of public health and environmental sustainability has increased the demand for organic products, particularly vegetables. CV Reja Mayur, as a producer of organic vegetables, plays a crucial role in meeting the needs of the growing market. In the competitive organic vegetable industry, innovative and sustainable marketing strategies are crucial. Green marketing, focusing on environmental sustainability and social responsibility, can be a solution to enhance brand visibility and build relationships with consumers who are concerned about sustainability. Community service activities were conducted at CV Reja Mayur, located in Desa Claket and Mligi, Kecamatan Pacet, Kabupaten Mojokerto, using the method of green marketing socialization. The results of this activity indicate that green marketing can highlight the positive impact of CV Reja Mayur's organic vegetable products on the environment. CV Reja Mayur can implement measures such as strengthening transparency, involving consumers in sustainability initiatives, utilizing social media, obtaining organic certification, and innovating in products and business processes. After receiving green marketing socialization, it is expected that CV Reja Mayur can enter a more sustainable marketing era and capitalize on the potential market that increasingly values organic products and sustainability.